An Innovative Disease‐Drug‐Trial Framework to Guide Binge Eating Disorder Drug Development: A Case Study for Topiramate. Issue 1 (9th September 2019) - Kalaria, Shamir N.; McElroy, Susan L.; Gobburu, Jogarao; Gopalakrishnan, Mathangi
Abstract : As with other psychiatric disorders, development of drugs to treat binge‐eating disorder (BED) has been hampered by high placebo response and dropout rates in randomized controlled trials (RCTs). Although not approved for use in BED, several RCTs have suggested that topiramate is efficacious for BED in obese individuals. Using data from a positive investigator‐initiated RCT of topiramate in 61 obese individuals with BED, the objective of the present study is (i) to develop a quantitative disease‐drug‐trial framework to inform future BED clinical trial designs, and (ii) to determine the optimal topiramate dose to achieve therapeutic efficacy. Disease‐drug‐trial models were developed separately for the two efficacy measures, namely, longitudinal normalized weekly binge‐eating episode frequency (BEF) and binge day frequency (BDF). Model building consisted of (i) developing a placebo effect model that describes response from the placebo group, (ii) adding a drug effect to the placebo model to describe dose‐response relationships, and (iii) developing a parametric time to event model to characterize patient dropout patterns. The placebo effect on normalized BEF and BDF over time demonstrated a maximum decrease of ~ 57% by 5 weeks. Participants had a higher dropout probability if no weight loss occurred during the trial period. The identified dose‐response relationship demonstrated a daily dose of 125 mg was needed to exhibit a marked reduction in weekly BEF. The developed comprehensive disease‐drug‐trial model will be utilized to simulate different clinical trial designs to increase the success for future BED drug development programs.